The web–based real estate multiple criteria negotiation decision support system: A new generation of decision support systems - Urbanavičienė, Vita; Kaklauskas, Artūras; Zavadskas, Edmundas K.; Seniut, Mark (International Journal of Strategic Property Management, 2009)
The negotiations are an inseparable part of the real estate buying and selling process. Currently real estate are characterized by the intensive creation and use of information, knowledge and automation (software, knowledge and decision support systems, neural networks, etc.) applications. It is commonly agreed that a better integration of information, knowledge and automation applications, as well use of voice stress analysis (one of biometric technologies) might be an efficient mean for decision making in real estate negotiations. Voice stress analysis can help the negotiators to distinguish between truth and lies, improve the value of decisions made, significantly speed up real estate sector processes, help to reach a better real estate sales and purchase agreement terms and decrease the overall cost of real estate search and negotiation processes. The authors’ objective is to improve the quality and efficiency of decision support systems. The article analyses scientific research related to negotiations and presents the developed Web–based Real Estate Multiple Criteria Negotiation Decision Support System with integrated voice stress analysis– a new generation of Decision Support Systems.First Publish Online: 18 Oct 2010